Gender Relationship Analysis in Coastal Resources Management in Fishermen's Households: Functional Structural Theory Perspective - Syaifudin Suhri Kasim; Sarmadan; Masrul; Ratna Supiyah; Tanzil (International Journal of Qualitative Research, 2021)
The results showed that gender relations in the management of coastal resources in fishing households took place in the following activities: fishing; making fishing lines; netting; net embroidery; fish transportation; fish preservation; and sale of fish. Of the seven activities, the wife plays a role in almost all coastal resource management activities, except for fishing activities. In addition, the wife does all domestic roles while the husband only focuses on the public role and does not involve himself in the domestic role. In view of the structural-functional theory, the results of this study illustrate that gender relations in coastal resource management in fishing households indicate a power relationship and status differences between men and women. The involvement of the wife (woman) in almost all activities is a form of integration (integration) carried out by the wife (woman) to maintain the continuity of the household and maintain the balance of the family integrity system, although this role is not balanced but complementary. The results of this study also show that gender relations in the management of coastal resources in fishermen's households have ideologically “perpetuated” male domination and gender stratification in fishermen's family institutions and society in general.